1987
DOI: 10.1073/pnas.84.7.2078
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of atrial natriuretic factor in brain microvessels.

Abstract: Cerebral capillaries constitute the blood-brain barrier. Studies of specific receptors (neurotransmitters or hormones) located on this structure can be performed by means of radioligand-binding techniques on isolated brain microvessels.We examined on pure bovine cerebral microvessel preparations the binding of atrial natriuretic factor (ANF), using 12I-labeled ANF. Saturation and competition experiments demonstrated the presence of a single class of ANF-binding sites with high affinity (dissociation constant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 25 publications
1
9
0
2
Order By: Relevance
“…In adults, ANP binds to the leptomeningeal surface of the brains and spinal cord (Mantyh et al 1987), where the hormone may play a role in regulating fluid/electrolyte exchange between blood vessels and the CSF. In addition, ANP binds to cerebral capillaries and may be involved with regulating microciruclation of the brain (Bianchi et al 1985;Chabrier et al 1987). Both the meninges and blood vessels are derived from the surrounding mesenthyme (Moore 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In adults, ANP binds to the leptomeningeal surface of the brains and spinal cord (Mantyh et al 1987), where the hormone may play a role in regulating fluid/electrolyte exchange between blood vessels and the CSF. In addition, ANP binds to cerebral capillaries and may be involved with regulating microciruclation of the brain (Bianchi et al 1985;Chabrier et al 1987). Both the meninges and blood vessels are derived from the surrounding mesenthyme (Moore 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Although astroglia cells numerically dominate the astroglia-rich culture (Hallermayer and Hamprecht, 1984;Loffler et al, 1986), the possibility has to be considered that the ANF-induced changes take place solely in other, minor cell populations that are known to be present, such as oligodendrocytes, ependymal cells, and phagocytes, or in cells whose presence cannot be ruled out, e.g., capillary endothelial cells and pericytes. The latter two cell types especially would be a focus of interest, because brain microvessels have binding sites for rANP (Chabrier et al, 1987). Nevertheless, the possibility that the rise in the level of cyclic GMP occurs only in a minor cell population is less likely for two reasons: (a) The maximal levels of cyclic GMP found in the rat cultures are somewhat (a factor of 1.5-2) higher even than in the clonal rat glioma cell line C6-BU-1 (Friedl et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…31 Atrial natriuretic peptide increases hematocrit, 32^3 as do paroxysms of AF. 34 Chabrier et al 35 found atrial natriuretic peptide receptors in the microvessels of the brain, and although the importance of this finding is unknown, there might be a relation between elevated atrial natriuretic peptide concentration, decreased cerebral blood flow, and the occurrence of cerebrovascular complications in patients with AF. 30 Studies relating the left atrial diameter to stroke risk have yielded conflicting results.…”
Section: Risk Factors For Stroke In Chronic Atrial Fibrillationmentioning
confidence: 99%